PATERNALISM OF THE CAREGIVER AND AUTONOMY OF THE ELDERLY IN THE HOME CARE SERVICE - Silva da Rocha, Tatiana (2024)
Due to the drop in birth and death rates, global population aging has been increasing on a large scale. In Brazil, it is estimated that, in 2050, the elderly population will total 21.87%. Aging changes epidemiological characteristics and intensifies health services, making it necessary to build care alternatives in the face of these challenges. The care provided to the elderly depends on their physical and psychological conditions and the caregiver's view of aging and their care skills.  From this view, paternalistic or elderly-centered care practices may emerge. This study investigated how caregiver paternalism occurs and its repercussions on the autonomy of elderly people monitored by the Home Care Service (SAD) in Fortaleza-CE. In field research with a qualitative and exploratory approach, semi-structured interviews were carried out with 6 elderly people and their caregivers. Data were collected at the patients' homes, between November and December 2023. According to the content analysis coding process by Bardin (2016), 03 thematic categories were obtained: 1) Caregiver's perception of the care provided to the elderly; 2) Paternalistic practices of the caregiver in caring for the elderly; 3) Repercussions of the caregiver's paternalism on the elderly's autonomy. The results confirm a paternalistic care practice characterized by overprotective attitudes, compromising the autonomy of the elderly. This makes us reflect on the importance of care that stimulates the autonomy of the elderly, understanding their subjectivity, preserving their dignity and guaranteeing their quality of life.